PENGGUNAAN ABSENSI SIDIK JARI (FINGER PRINT) DAN MOTIVASI TERHADAP DISIPLIN KERJA ASN DI SEKRETARIAT DAERAH KABUPATEN KERINCI: M. DHANY ALSUNAH, S.Pd., M.Pd - M Dhany Alsunah (LPPM STIA Nusantara Sakti, 2019)
The Effect of Fingerprint Attendance and Motivation on ASN Work Discipline in he Kerinci Regency Regional Secretariat. This research was conducted at the erinci Regency Regional Secretariat with the formulation of the research problem. 1. Is there a simultaneous and partial influence between fingerprint attendance and motivation on ASN work discipline at the Kerinci Regency Regional Secretariat 2. How much is the simultaneous and partial influence between fingerprint attendance and motivation on ASN work discipline at the Kerinci Regency Regional Secretariat : 1. To determine the effect simultaneously and partially between fingerprint attendance and motivation on ASN work discipline in the Kerinci Regency Regional Secretariat 2. To know the magnitude of the partial and simultaneous influence between fingerprint attendance and motivation on ASN work discipline on the influence simultaneously and partial between fingerprint attendance and motivation towards ASN work discipline at the Kerinci Regency Regional Secretariat. This research uses a quantitative approach where data is obtained through a field questionnaire to 35 respondents who refer to the research indicators of fingerprint attendance, motivation and work discipline variables. Data obtained in the field were analyzed based on formulas. Multiple Linear Regression to see the effect of the variables X1, X2 on the Y variable. KD (Coefficient of Determination) to see the magnitude of the influence between the variables X1, X2 on the Y variable. From the results of the study note that fingerprint attendance and motivation affect the ASN work discipline on the influence Simultaneously and partially between fingerprint attendance and motivation towards ASN work discipline in the Kerinci Regency Regional Secretariat, the influence was 31.1% ,. For this reason the authors suggest that fingerprint attendance and motivation can be increased so that work discipline can run optimally and with quality.